An Analysis of Code Switching and Code Mixing used by Students from North Sumatra in State Universityb of Padang - Nainggolan, Krisepan; Fitrawati, Fitrawati (Universitas Negeri Padang, 2021)
This study aims to determine the phenomenon of code switching and code mixing in the Toba Batak student community at Padang State University. The method used in this research is descriptive. The data from this study are utterances or expressions of conversation between Toba Batak students who can be seen on the dialogue transcript. Code switching was found in this study as many as 24 data, while the mixed code was found as many as 29 data. Research findings show that conversations between students of the Toba Batak community at Padang State University more often use 29 data mixed codes, while 24 code changes are found. Furthermore, for the type of code switching found inter-sentential switching as the type that appears the most as many as 13 data (54.17%), while for the mixed code type found the insertion of words is the most frequently used as many as 21 data (72.42%). Next, for the reason that code switching is most often found is talk about particular topic as many as 15 data (62.5%), while for the purpose of mixed code that is often found, the socio expressive function is 19 data (65.5%).